Knowledge Management: thematic configuration and emerging issues - Brunni Cartaxo de Castro, Ahiram (2022)
Knowledge management has become a discipline of reference that supports the search for understanding organizational performance, innovation, and competitive advantage. This research aimed to map the production over knowledge management in the ISI Web of Science database with a seven-year temporal cut that highlights the emerging theme about research advancements on the topic. There was a comprehensive information survey through a bibliometric study using the HistCiteTM and the QSR NVivo® software. The main results confirm the perception of the knowledge management's gradual maturation process as an independent academic discipline. This study's theoretical contribution lies in the proposition of a framework that represents the theme configuration. This research also fills the gap about scientometric works over knowledge management in the period researched and codifies the emerging themes.